Rural Entrepreneurial Motivations On Account of Rural Entrepreneurial Profile: A study with special reference to Kerala. - Asha A G
The present study was undertaken to understand rural entrepreneurial motivations on account of rural entrepreneurial profile, with special reference to Kerala. The analysis and interpretation of data collected from 270 rural entrepreneurs brought out fruitful findings relating to rural entrepreneurial motivations on account of rural entrepreneurial profile. The researcher framed and tested the hypothesis regarding the motivators such as enabling environment, autonomy and intellectual drive and social anchoring with the entrepreneurial profile, in which nine cases accepted null hypothesis and twelve cases rejected the same in favour of alternative hypotheses.